Historical dictionary of quotations in cognitive science : a treasury of quotations in psychology, philosophy, and artificial intelligence - Wagman, Morton (Greenwood Press, 2000)
Scholarly treasury of over 450 distinguished quotations. Focuses on the best thinking in the disciplines of psychology, philosophy, and artificial intelligence, from the classical period of Greece to contemporary cognitive science.